Biological security of pig farms - D. A. Lozovoy; A. K. Karaulov; K. N. Gruzdev (Ветеринария сегодня)
The paper describes aspects of biological security in pig farming in conditions of worsening of epizootic situation associated with swine viral diseases and African swine fever (ASF) occurrence, as well as the history of ASF occurrence and spread over the RF territory, emergency and control measures against swine infectious diseases, which are developed and implemented by the Rosselkhoznadzor and Veterinary Department of the RF Ministry of Agriculture. Efficiency assessment of measures and evaluation of current situation in the field of pig farming was performed.